Árvores zoocóricas como núcleos de atração de avifauna e dispersão de sementes - Andrade, Marco Antônio de (2003)
The avian fauna as fruit-eating and seed dispersai plays a major role in plant demography and, consequently. in plant community dynamic. In tropical moist forests, from 70% to over 90% of the species of shrubs and trees are depending on fruit-eating vertebrates to disperse their seeds. In neotropical forests, from 20% to 30% of avian species use fruit in their diets. The aim of this research work was to proceed an evaluation of potential selectedfruit producing trees, to play a role as avian faunas and seed dispersai attraction nucleous. The field research work was carried out from March of 2001 to July of 2002 in Lavras city, Minas Gerais State, at the campus of Federal University of Lavras, Brazil. In this research work, twelve fruit-producing trees were selected: Trema micrantha, Alchornea triplinervea, Myrcia rostrata, Miconia argyrpphylla, Persea pyrifolia, Senna macranthera, Syagrus romanzoffiana, Solanum granuloso-leprosum, Vismia brasiliensis, Michelia champaca, Muntingia calabura and Morus nigra. For each selected tree it was spent 35 hours of observations subdivided in 35 sampling units of one hour period. To evaluate frugivory and seed dispersai events, on each selected tree, was utilized a method denominated "focal-tree". A total of 84 and 49 avian species was observed as visiting tree and fruit eating, respectively. Thraupis sayaca and Tangara cayana play an important role as visiting trees, fruit consumers and seed dispersais. This research work shows that, among the studied tree species, Trema micrantha, Alchornea triplinervea, Myrcia rostrata, Michelia champaca and Miconia argyrophila play a major role as avian faunas and seed dispersai nucleous. Thus, these tree species are highly recommended to compound land restorations plans and programs.